DEVELOPING SUPPLEMENTARY TEACHING SPEAKING I MATERIALS FOR STUDENTS OF ENGLISH EDUCATION PROGRAM OF IAIN BENGKULU - Efrizal, Dedi (Linguists : Journal of Linguistics and Language Teaching, 2020)
Most of third semester students of English Education program of State Institute for Islamic Studies (IAIN) Bengkulu, Indonesia, encountered many problems in speaking activity. The main problem was there were not appropriate teaching English speaking materials yet that give big portion and opportunity for the students to speak actively and freely based on their contextual or daily experiences and background in order to support teaching and learning process of English speaking I. the objective of this research is developing a set of supplementary teaching English speaking materials for the students based Contextual Teaching and Learning. This research used Research and Development design with the procedures: conducting need assessment, developing supplementary materials, conducting expert validation, revising the materials, trying out the materials, and revising the materials. The researcher collected the data by using questionnaires, interview, analyzing the syllabus, and field note. The product of this research is four units of supplementary teaching English speaking I materials for third semester students of English Education program of State Institute for Islamic Studies Bengkulu, Indonesia.